Labor employment in the manufacturing sector of Malaysia - Yusoff, Mohammed; Syed Salleh, Sharifah Nabilah (International Institute of Academic Research and Development, 2017)
The manufacturing sector has been contributing significantly to the Malaysia’s economy in terms of its contribution to GDP, employment, and exports. This paper examines the determinants of employment of labor in the Malaysian manufacturing sector.We estimate the model using the instrumental variable technique and the results suggest that the real wage rate, output represented by the value added , and capital represented by the value of fixed assets are all important determinants of labor employment in manufacturing sector in Malaysia.This implies that implementing policies to encourage capital accumulation and overall economic growth are indeed helpful to boost employment in the manufacturing sector. The elasticity of labor employment with respect to wage rate is 1.86 suggesting that labor employment is responsive to the changes in wage rate; a 1% decrease in wage rate increases employment by 1.86% which will then spur the manufacturing output which are mostly exported to foreign countries. This suggests that employment in the manufacturing sector could be created through wage reduction , increase in capital and output level.